Effect of different plant extracts, fatty acid and oils on conjugated linoleic acid (CLA) production by Butyrivibrio fibrisolvens - TYAGI, AMRISH KUMAR; SHANDILYA, U K; SRIVASTAVA, A; TYAGI, A; KUMAR, M; RASTOGI, S; RAWAT, A K S; SINGH, R R B (The Indian Journal of Animal Sciences, 2015)
Present study evaluated the effect of added free fatty acids, dietary oils and plant extracts on conjugated linoleic acid (CLA) production potential of anaerobic Butyrivibrio fibrisolvens bacteria. Different concentration of plant extracts of Solanum nigrum, Rumex dentatus, Boerhaavia diffusa Linn., Amaranthus nlitum Linn., Peristrophe bicalyculata, Phyllanthus sp. Leucas aspera and Cuminum cyminum (0.50, 1.0, 1.5%, 2.0, 4.0, 6.0, 8 and 10 mg/ml of media); pure linoleic and linolenic acid (50, 100, 150, 200, 250 μg/ml of media) and dietary oils (50, 100, 150, 200, 250, 300 μg/ml of media) were used in media. The results revealed that an increase in the concentration of fatty acids suppressed growth of B. fibrisolvens and its cell density reached maximum (1.58 OD; 600 nm) at 18 h of incubation. A gradual rise in CLA production by B. fibrisolvens was observed parallel to increasing concentration of dietary oils from 50 to 250 μg/ml followed with slight decrease at level of 300 μg. Supplementation of sunflower oil resulted in highest increment in CLA production among the treatments. Extracts of different plants at different concentrations showed significant changes in CLA production potential by B. fibrisolvens. Cuminum cyminum with 457% increase in CLA concentration was the most efficient extract. Study established that careful optimization of dietary supplementation results in increased activity of B. fibrisolvens thereby facilitating higher CLA production.